Pengaruh Kualitas Pelayanan, Promosi dan Citra Merek Terhadap Keputusan Pembelian di The Tribrata Dharmawangsa Jakarta - Triyanto; Bonifasius MH Nainggolan (Human Capital Development, 2023)
This study aims to determine the role of service quality, price perception, and customer experience on customer satisfaction. The sample technique used in this study is a purposive sample method with the number of respondents to the final sample being 70 people. Based on the sampling method set, the study was conducted through a survey of The Tribrata Dharmawangsa Jakarta consumers who had stayed at least ones. The data analysis method was carried out by multiple linear regression analysis with the help of SPSS software version 25. After going through the examination of classical assumptions in multiple linear regression models, the results showed that service quality had a positive and significant effect on buying decision at The Tribrata Dharmawangsa Jakarta. The same results were also obtained for promotion variables. These two variables together have a significant effect on buying decision. Of the three variables studied, the most dominant service quality factor determines buying decision, followed by promotion and brand image.